Ferrocene as a leaving group; Unexpected rearrangement reactions for the synthesis of 2,3-diarylnapthoquinones - Nevroz Aslan Ertaş; Arif Kıvrak (MANAS: Journal of Engineering)
In general, Suzuki-Miyaura coupling reaction between aryl bromide and arylboronic acids form the new C-C bond in the presence of Pd-catalyst. In the present study, 2-bromo-3-ferrocenyl-1,4-naphthoquinone 2 intermediate is synthesized by starting from 2,3-dibromo-1,4-naphthoquinone via Suzuki-Miyaura Coupling reaction. Then, it is investigated that the reaction between 2 and arylboronic acids give a new rearrangement reaction involving free radicals. Ferrocene structure displays critical roles for the formation of 2,3-diaryl-1,4-naphthoquinones. This reaction could be first example for the radical C-C bond cleavage reactions including ferrocene.